PROBLEMATIKA GURU PENDIDIKAN AGAMA ISLAM (PAI) PADA PEMBELAJARAN DARING DI MASA PENDEMI COVID-19 SMPN 9 BANJARBARU - Hayati, Anisah Norlaila; Toriqularif, Muhammad; Khairunnisa, Khairunnisa (ADDABANA: Jurnal Pendidikan Agama Islam, 2021)
Abstract: When learning, teachers and students are often faced with various problems both related to subjects and social relations. Moreover, when the Covid-19 pandemic hit, there were several obstacles so that online learning could not run optimally. So it is necessary to review this issue in more depth. The focus of this research is the problems of PAI teachers in online learning during the Covid-19 pandemic at SMPN 9 Banjarbaru. So the aim of this research is to find out the problems of PAI teachers in online learning during the Covid-19 pandemic at SMPN 9 Banjarbaru as well as the supporting and inhibiting aspects. The subjects in this research were 2 Islamic Religious Education teachers. In extracting data, researchers used observation, interview and documentation techniques. Data management techniques are carried out by data classification, editing, and data interpretation. Next, it was analyzed using qualitative descriptive analysis and conclusions were drawn inductively.Based on the research results, it is known that the problems of PAI teachers in online learning during the Covid-19 pandemic at SMPN 9 Banjarbaru, the problems of PAI teachers in online learning at SMPN 9 Banjarbaru are not optimal in their implementation because there are several problems faced by Islamic religious education teachers, such as: 1) Lack of attention parent. 2) unwise use of learning media. 3) Lazy about doing school work. 4) Unstable Network. 5) The state of the family's economic conditions. It can be seen that Islamic Religious Education Teachers carry out online learning by carrying out implementation, assignments and problems in assessments. Aspects that support Islamic Religious Education Teachers' problems in Online Learning include, among others, the educational background, teaching experience and personality of Islamic Religious Education teachers. Apart from that, learning media and the family environment, especially parents, are also aspects that hinder PAI teacher problems in online learning during the COVID-19 pandemic at SMPN 9 Banjarbaru. The inhibiting aspect is the low level and unwise use of learning media, because the free use of cellphones as learning media can make students unfocused and lazy with the tasks given by the teacher. Apart from that, an unstable network also makes it difficult for students to do their assignments. Keywords: Islamic Education Teacher, Online Learning, Problems. Abstrak: Saat dalam pembelajaran guru dan peserta didik sering dihadapkan pada berbagai masalah baik yang berkaitan dengan mata pelajaran maupun yang menyangkut hubungan sosial. Apa lagi pada saat pandemi covid-19 melanda ada beberapa kendala sehingga pembelajaran daring tidak dapat berjalan dengan maksimal. Sehingga perlu untuk ditinjau lebih mendalam terkait masalah tersebut. Fokus dalam penelitian ini adalah bagaimana problematika guru PAI dalam pembelajaran daring pada masa pendemi Covid-19 di SMPN 9 Banjarbaru. Maka tujuan penelitian ini ialah untuk mengetahuai problematika guru PAI  pada pembelajaran daring dimasa pendemi Covid-19 SMPN 9 Banjarbaru serta aspek pendukung dan penghambatnya. Subjek dalam penelitian ini ialah 2 guru Pendidikan Agama Islam. Dalam penggalian data, peneliti menggunakan teknik observasi, wawancara dan dokumentasi. Teknik pengelolaan data dilakukan dengan klasifikasi data, editing, dan interpretasi data. Selanjutnya dianalisis dengan analisa deskriptif kualitatif dan ditarik simpulan secara induktif.Berdasarkan hasil penelitian diketahui bahwa Problematika Guru PAI pada Pembelajaran Daring dimasa Pendemi Covid-19 SMPN 9 Banjarbaru, Problematika Guru PAI pada pembelajaran daring di SMPN 9 Banjarbaru dalam pelaksanaanya kurang maksimal karena ada beberapa problem yang dihadapi Guru pendidikan agama Islam seperti: 1) Kurangnya perhatian orang tua. 2) penggunaan media pembelajaran yang kurang bijak. 3) Malas mengerjakan tugas sekolah. 4) Jaringan tidak Stabil. 5) Keadaan kondisi Ekonomi keluarga. Terlihat dari Guru Pendidikan Agama Islam melaksanakan pembelajaran daring dengan melakukan pelaksanaan, penugasan dan problematika pada penilaian.Aspek yang mendukung problematika Guru PAI pada Pembelajaran Daring antara lain berasal dari latar belakang pendidikan, pengalaman mengajar, dan kepribadan guru Pendidikan Agama Islam. Selain itu media pembelajaran, dan lingkungan keluarga terutama orangtua yang juga menjadi aspek penghambat Problematika Guru PAI pada pemnelajaran daring dimasa pendemi COVID-19 SMPN 9 Banjarbaru. Aspek yang menghambat adalah rendah dan penggunaan media pembelajaran yang kurang bijak, karena penggunaan handphone sebagai media pembelajaran secara bebas dapat membuat siswa tidak fokus dan malas dengan tugas-tugas yang diberikan guru. Selain itu, jaringan yang tidak stabil juga membuat siswa kesulitan pada saat mengerjakan tugas. Kata Kunci: Guru PAI, Pembelajaran Daring, Problematika.